The role of Bifidobacterium lactis B94 plus inulin in the treatment of acute infectious diarrhea in children - Ali İşlek,; Ersin Sayar,; Aygen Yılmaz,; Betil Özhak Baysan,; Derya Mutlu,; Reha Artan, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: In contrast to many other studies of probiotic species, the number of publications evaluating Bifidobacterium lactis and its combinations with prebiotics as treatments for acute infectious diarrhea is limited. We investigated the synbiotic effects of B. lactis B94 plus inulin on acute infectious diarrhea. Materials and Methods: The study was conducted on children with acute diarrhea between the ages of 2 and 60 months. The patients were administered 5×1010 colony-forming units (CFU) of B. lactis B94 plus 900 mg inulin or placebo, once a day for five days. Stools were examined for Rotavirus, Adenovirus, Entamoeba histolytica, Salmonella, Shigella, Campylobacter, Clostridium difficile, Cryptosporidium, and parasites. Results: We examined 79 patients in the synbiotic group and 77 patients in the placebo group. The duration of diarrhea was significantly reduced in the synbiotic group in comparison with the placebo group (3.9±1.2 days vs. 5.2±1.3 days, respectively; p<0.001). Moreover, the number of diarrheal stools on the third day was significantly lower in the synbiotic group than in the placebo group (5.5±2.9 vs. 8.3±3.01, respectively; p<0.001). Diarrhea in the synbiotic-group patients with rotavirus infection was of a significantly shorter duration (3.2±1.3 days vs. 5.2±1.3 days, respectively; p=0.001). Duration of diarrhea in patients who started the synbiotic treatment within the first 24 h was shorter than that in the patients who started the treatment later (3.9±1.1 days vs. 4.8±1.8 days, respectively; p=0.002). Conclusion: Treatment with 5 × 1010 CFU of B. lactis B94 plus 900 mg inulin shortened the duration of acute watery diarrhea by an average of 31 h. This decrease was most pronounced in cases of Rotavirus diarrhea.